Challenging desire : performing whiteness in post-apartheid South Africa - Smit, Sonja (Rhodes University, Faculty of Humanities, Department of Drama, 2014)
The central argument of this thesis asserts that in the process of challenging dominant subject positions, such as whiteness, performance creates the possibilities for new or alternative arrangements of desire. It examines how the creative process of desire is forestalled (reified) by habitual representations of whiteness as a privileged position, and proposes that performance can be a valid form of resistance to static conceptions of race and subjectivity. The discussion takes into account how the privilege of whiteness finds representation through forms of neo-liberalism and neo-colonialism in the post apartheid context. The analysis focuses on the work of white South African artists whose work offers a critique from within the privileged "centre" of whiteness. The research is situated within the inter-disciplinary field of performance studies entailing a reading and application of critical texts to the analysis. Alongside this qualitative methodology surfaces a subjective dialogue with the information presented on whiteness. Part Two includes an analysis of Steven Cohen's The Cradle of Humankind (2011), Brett Bailey's Exhibit A (2011) and Michael MacGarry's LHR-JNB (2010). Each section examines the way in which the respective works engage in a questioning of whiteness through performance. Part Three investigates South African rap-rave duo, Die Antwoord and how their appropriation of Zef interrogates desires for an essential authenticity. Part Four focuses on my own performance practice and the proposed value of engaging with a form of practice-led research. This is particularly relevant in relation to critical race studies that require a level of self-reflexivity from the researcher. It presents an analysis of the work entitled Villain (2012) as a disturbance of theatrical desire through a process of 'becoming'. This notion of meaning and identity as 'becoming' is argued as a strategy to challenge prevailing modes of perception which can possibly restore the production of desire to the viewer. The thesis concludes with the notion that performance can offer a mode of immanent ethics which is significant in creating both vulnerable and critical forms of whiteness.
Keywords: Performance art -- South Africa; Bailey, Brett, 1967-; Cohen, Steven, 1962-; Antwoord (Musical group); MacGarry, Michael; Eurocentrism -- South Africa